Comparative effects of capacitive and inductive superstrates on the RCA's gain. Issue 11 (17th May 2018) - Zhou, Lin; Chen, Xing; Cui, Yuguo; Duan, Xin
Abstract : The radiation performance of the resonant cavity antenna (RCA) is mainly determined by the superstrate, and thereby various superstrates are designed for the RCA to obtain high performance. In this work, the comparative effects of the capacitive and inductive superstrates on the RCA's gain are investigated systematically. Three approaches including the leaky‐wave model, full‐wave simulations and prototype measurements are employed for the investigation. Using the leaky‐wave model, the gains of the RCA with various superstrates are calculated and a difference between the gains with the capacitive and inductive superstrates is observed. Full‐wave simulations and prototype measurements further prove the result. All the approaches demonstrate that the capacitive superstrate has the potential to obtain a higher gain, in comparison with the inductive superstrate having the same reflection magnitude and aperture size.